2012
DOI: 10.1074/mcp.m111.010918
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Expression and Carbonylation Changes During Trypanosoma cruzi Infection and Chagas Disease in Rats

Abstract: Inflammation and oxidative stress, elicited by Trypanosoma cruzi infection, are important pathologic events during progressive Chagasic cardiomyopathy. In this study, we infected Sprague-Dawley rats with T. cruzi, and treated with phenyl-␣-tert-butylnitrone (PBN-antioxidant) and/or benznidazole (BZ-anti-parasite). We employed two-dimensional gel electrophoresis/mass spectrometry to investigate (a) the plasma proteomic changes associated with infection and disease development, and (b) the beneficial effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 62 publications
1
16
0
1
Order By: Relevance
“…Significantly increased protein carbonylation levels were detected in the blood plasma of rats infected with Trypanosoma cruzi, of which 48 modified proteins were involved in transport (19%), inflammatory response (14%), complement activation (14%), metabolism (10%), tissue remodeling (10%), apoptosis (9%), acute-phase response (9%), DNA catabolic process (5%), myosin complex (5%), and response to cytokine stimulus (5%). Increased levels of oxidized proteins in specific biological processes, such as inflammatory response, complement activation, acute-phase, and cytokine response, in the course of infectious diseases supports the hypothesis of specific protein carbonylation (Wen & Garg, 2012). In a transgenic PS1 þ AbPP mouse model of Alzheimer's disease a total of 117 carbonylated proteins were identified by combining 2D Western blot analysis and MS. Pathway and network analysis revealed that three main networks were potentially altered during AD development: the iNOS-integrin signaling pathway, CRE/CBP transcription regulation and rab-lyst vesicular trafficking.…”
Section: Systems Biologymentioning
confidence: 69%
“…Significantly increased protein carbonylation levels were detected in the blood plasma of rats infected with Trypanosoma cruzi, of which 48 modified proteins were involved in transport (19%), inflammatory response (14%), complement activation (14%), metabolism (10%), tissue remodeling (10%), apoptosis (9%), acute-phase response (9%), DNA catabolic process (5%), myosin complex (5%), and response to cytokine stimulus (5%). Increased levels of oxidized proteins in specific biological processes, such as inflammatory response, complement activation, acute-phase, and cytokine response, in the course of infectious diseases supports the hypothesis of specific protein carbonylation (Wen & Garg, 2012). In a transgenic PS1 þ AbPP mouse model of Alzheimer's disease a total of 117 carbonylated proteins were identified by combining 2D Western blot analysis and MS. Pathway and network analysis revealed that three main networks were potentially altered during AD development: the iNOS-integrin signaling pathway, CRE/CBP transcription regulation and rab-lyst vesicular trafficking.…”
Section: Systems Biologymentioning
confidence: 69%
“…Two, increase in plasma LPO/MDA levels in seropositive/chagasic subjects may also be due to oxidatively-modified lipids released as a consequence of cellular injuries incurred in the cardiac tissue. This notion is supported by the observation of intense oxidative modifications of DNA, lipids and proteins in chagasic myocardium [13], [15] and identification of multiple oxidatively-modified cardiac proteins in sera/plasma of chronically-infected animals [27][28] and humans [18]. Three, SOD and GPX/GSH antioxidants, utilized by mammalian cells to cope with free radicals, were compromised in chagasic myocardium [14], [17].…”
Section: Discussionmentioning
confidence: 88%
“…Treatment with PBN controlled the pathologic oxidative tissue injury and preserved mitochondrial respiratory chain function in both acutely and chronically infected rodents. Wen and Garg [64] also showed that PBN restored the differential expression of 65% of the disease-associated proteins to the normal level and prevented the development of oxidative adducts on plasma proteins in chronically infected rats [51,64]. Importantly, PBN alone or in combination with benznidazole (but not benznidazole alone) preserved the left ventricular function that otherwise was significantly compromised in chronically infected Chagas rats [51,64].…”
Section: Phenyl-alfa-tert-butyl Nitrone (Pbn)mentioning
confidence: 96%
“…PBN is a nitronebased antioxidant that scavenges free radical species and inhibits free radical generation [63]. The effects of PBN in CD have been reported in rats during the acute and chronic phases of infection using an oral administration of 1.3 mM of PBN for three weeks [51,64] and in mice during the acute phase with injection delivery of 50 mg/kg of PBN [50]. Treatment with PBN controlled the pathologic oxidative tissue injury and preserved mitochondrial respiratory chain function in both acutely and chronically infected rodents.…”
Section: Phenyl-alfa-tert-butyl Nitrone (Pbn)mentioning
confidence: 99%